2017
DOI: 10.1088/1361-651x/aa6ef8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular statics study of depth-dependent hysteresis in nano-scale adhesive elastic contacts

Abstract: The contact force—indentation-depth (P–h) measurements in adhesive contact experiments, such as atomic force microscopy, display hysteresis. In some cases, the amount of hysteretic energy loss is found to depend on the maximum indentation-depth. This depth-dependent hysteresis (DDH) is not explained by classical contact theories, such as Johnson–Kendall–Roberts and Derjaguin–Muller–Toporov, and is often attributed to surface moisture, material viscoelasticity, and plasticity. We present molecular statics simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Experiments of Purtov et al [15] and modelling of the experiments by Pepelyshev et al [16], employing Galanov's model of adhesion between rough surfaces [17], showed that consideration of real contact area is a very important factor in adhesive contact problems. This statement is also nicely confirmed by the analysis of nanoscale static friction by Polyakov et al [18], and various works that demonstrate the influence of roughness on the value of adhesive pull-off force (e.g., [19][20][21]).…”
Section: Introductionsupporting
confidence: 57%
“…Experiments of Purtov et al [15] and modelling of the experiments by Pepelyshev et al [16], employing Galanov's model of adhesion between rough surfaces [17], showed that consideration of real contact area is a very important factor in adhesive contact problems. This statement is also nicely confirmed by the analysis of nanoscale static friction by Polyakov et al [18], and various works that demonstrate the influence of roughness on the value of adhesive pull-off force (e.g., [19][20][21]).…”
Section: Introductionsupporting
confidence: 57%
“…Motivated by the observation of overlapping hysteresis loops during consecutive load-unload cycles both in air and underwater, they hypothesized that DDH was due to the occurrence of a series of small-scale surface, mechanical instabilities that are created due to surface roughness, adhesion, and the large compliance of the soft materials involved 16 . Our recent static molecular simulations showed that this mechanism can operate in adhesive elastic contacts 17 . The surface instabilities through which small-scale roughness gives rise to DDH in the work of Kesari et al 6 and Kesari and Lew 16 are the same as those through which surface undulations cause adhesive toughening in the work of Li and Kim 18 and Guduru 19 .…”
Section: This Phenomenon Depth-dependent Hysteresis (Ddh)mentioning
confidence: 95%
“…In addition, the adhesion between solids is generally measured using axisymmetric, contact mechanics-based methods [68]. However, surface roughness is known to cause considerable difficulties in unambiguously measuring w using such methods [69][70][71]. Therefore, it would be interesting to see how competitive the proposed vibration-based method for measuring w would be in comparison to the contact mechanics-based methods.…”
Section: Discussionmentioning
confidence: 99%